Maximal Sensitivity to Child Maltreatment at the Ages of 6 and 11 Years is Associated with the Risk of Bipolar Disorder - Montoro, Irene (Journal of interpersonal violence, 2023)
Adverse childhood experiences, including child maltreatment (CM), are relevant environmental risk factors for bipolar disorder (BD). However, little is known about the interaction of the type, duration and frequency of abuse with the timing of abuse in BD. The aim of this study was to investigate the different patterns of childhood trauma (frequency, type and chronology) between BD patients and healthy controls (HCs) and to identify BD-sensitive periods of exposure to CM that could influence functioning outcomes. The Maltreatment and Abuse Chronology Exposure (MACE) scale was used to evaluate the importance of the type and timing of maltreatment in a sample of 60 patients diagnosed with euthymic BD. Additionally, 76 HCs were recruited for comparison. All participants were of European-Caucasian origin and were assessed in the 2016-2019 period. To identify the variables that maximally differentiated the type and timing of exposure to CM between the BD and HC groups, a linear mixed effects model and random forest (RF) analyses were applied. We showed that multiplicity and severity, nonverbal emotional abuse, witnessing interparental violence and emotional neglect were the main factors associated with BD. In addition, regarding the occurrence of maltreatment in BD patients, we identified two sensitive periods with a principal peak at the age of 6 and a secondary peak at the age of 11. Functionality at the assessment time was associated with CM in adolescence for both HC and BD participants. Although the sample size and retrospective nature of the MACE instrument were the main limitations of our study, we were unable to explore the role of variables such as sex or socioeconomic status. We concluded that the multiplicity and sensitivity of CM exposure, mainly of the emotional type, during middle childhood are important risk factors for BD, at least in the European-Caucasian cultural setting.